Integrating children’s values in policymaking: challenges and opportunities in a diverse society - Alvarez, E.; Ramos, A.; Tendais, I.; Rodrigues, R. B. (VIII Congreso de la Red Española de Política Social, 2021)
Values are a central dimension of human social life, they are core to a persons' selfconcept and identity and drive individual actions towards both personal enhancement and social transformation. At a social level, values govern how individuals relate to others and shape the organization of societies being, therefore, powerful guidelines to face new societal challenges like inclusion/exclusion issues, social justice or cultural diversity. Research with adults in this field has demonstrated that human values are powerful predictors of a wide range of behaviours, attitudes and beliefs. However, research with children is still very recent and has mostly focused on adolescents and older children. Little attention has been given to the youngest, probably due to concerns on young children's capabilities to produce reliable information and discourse. Seen as 'not adults' or 'adults in the making' research has hidden children's voices instead of recognizing that they have views that differ from the adults but are as valid as adults ones. Fortunately, new approaches in childhood research emphasize the importance of recognizing children as social actors that are able to give their opinion about diverse societal issues, especially when it implies expressing their views on matters that affect them. In the same way, children's voices regarding political issues have been frequently dismissed even when children's right to participate fully in political and cultural life is specifically recognized in the United Nations Convention on the Rights of the Child. Therefore, giving voice to children is ultimately a matter of respecting their rights. To address this gap we introduce in this presentation a project that seeks to respond to this need by mapping the basic human values (e.g. Schwartz, 1992) of children and young adolescents (6 to 14 years) and its associations with the representations of justice and attitudes towards social groups that experience different forms of stigmatization or social exclusion. The longitudinal design of this project will enable the examination of the developmental dimension of value priorities formation and the contribution of parents and teachers to this process. The relevance of the school context and the introduction of the perspective of the teachers in the project will allow us to a better understanding of how the present curricula of the basic educational level addresses the issue of values and citizenship within young populations. In our view, to develop transnational research in these fields is not just needed in order to improve our knowledge about values’ formation and development but also to inform national and european social policies aimed at creating more inclusive societies. Incorporating values and children views on the present and future of the societies in the school curricula may represent a valuable opportunity to strengthen children’s rights, foster citizenship and ultimately to strengthen democracy. In this presentation we intend to propose further directions in policymaking by discussing how children could be involved in decision-making to engage the development of bottom-up policies and how to frame social policies that operationalize human rights and values conceptions.